Produtividade e rentabilidade de cultivares de soja em zonas de manejo - Fioresi, Dejales (2019)
The yield potentials of soybean (Glycine max (L.) Merrill) have been enabling the introduction of new genotypes each year/crop. However, the high cost for cultivation, mainly of the seed, require assertive decision-making and, to the cultivation environment, its variability and the correct choice of cultivars for higher productivity results. The study was conducted in areas of commercial production in the 2015/2016 crop, located in the municipality of Boa Vista das Missões-RS, using 36 cultivars and, in the 2016/2017 crop, using 18 cultivars, installed in the municipality of Condor-RS and in the municipality of Boa Vista das Missões-RS. The productivity and profitability of soybean cultivars associated with planting in management zones were evaluated. We can observe that the results between the zones were higher in productivity and performance for most cultivars in the high zone, with significant differences (in the first crop) and smaller differences and with lower amount of cultivars exceeding the low zone (in the second harvest), showing that the condition of the production environment can be determinant for the expression of the productive potential of most soybean cultivars studied.